Paired growth of cultivated and halophytic wild rice under salt stress induces bacterial endophytes and gene expression responses - Tasnim, Anika; Jahan, Israt; Azim, Tomalika; Karmoker, Dola; Seraj, Zeba I. (Frontiers in Plant Science, 2023)
Utilizing salt-affected marginal lands in coastal regions can help meet the growing demand for rice. We explored a nature-based solution involving wild halophytic rice (O. coarctata, Oc) and commercial rice BRRI Dhan 67 (O. sativa, Os) grown in close proximity to each other under salt stress, to investigate whether such a planting strategy could help complement rice growth and yield under stress. We also investigated the gene expression and endophytic bacterial profiles of both Os and Oc in unpaired and paired conditions without and with salt. Paired plants exhibited lower salt damage indicators such as smaller reduction in plant height, electrolyte leakage and chlorophyll loss, as well as higher K + /Na + ratio under saline stress. Some of the 39 endophytic bacteria in the mutualism experiment were unique to Oc and transferred to Os when paired.Os versus unpaired Os were 1097 (994 upregulated, 101 down-regulated) without salt and 893 (763 up-regulated, 130 down-regulated) under salt stress. The presence of Oc plants under salt stress influenced major biological processes in Os, including oxidative stress; chitinase activity; phenylalanine catabolic process and response to ABA. Protein binding and serine/threonine kinase activity were primarily affected in molecular function. The downregulated WRKY transcription factor 22 in paired conditions under salt stress played a role in the MAPK signaling pathway, reducing respiratory cell death. The upregulated auxin-responsive protein IAA18 gene, involved in hormone signaling and cell enlargement, was present only in paired plants. Our findings therefore, offer insights into developing more effective cultivation strategies for sustainable rice production.